Making the Car "Platform Ready": How Big Tech Is Driving the Platformization of Automobility. (June 2022) - Hind, Sam; Kanderske, Max; van der Vlist, Fernando
"Big Tech" platform companies like Alphabet (Google), Apple, and Amazon are deeply invested in the future of automobility—from developing car-specific interfaces and self-driving technology to establishing business partnerships with automakers. Far from business-as-usual, we explain how Big Tech is reshaping the traditional automotive industry by making the car "platform ready, " as imposed on the web before it. The article considers how this novel transformation of automobility is increasingly significant for critical scholars of social media, platforms, and platformization, as bespoke forms of mediated, datafied, and platformized, sociality emerge. Specifically, we identify six levels upon which this platformization of automobility is unfolding and through which Big Tech is reorganizing the automotive industry according to platform logics concerning programmability, modularity, connectivity, data collection, and developmental partnerships. We do so by analyzing academic and technical literature, industry reports, and initiatives with a stake in platform automobility . Finally, we suggest directions for further research into Big Tech's stake in the future of automobility, as these new dynamics begin to reshape the automotive industry at large.